Determinants of corporate liquidity: a literature review - Nguyen, Thi Thu Huyen (Journal of International Economics and Management, 2015)
The 2008-9 financial crisis has renewed interest in the way in which firms manage liquidity, because firms’ access to external financing was a major determinant of firms’ survival during this period. Yet, research on determinants of corporate liquidity is an old topic and has been discussed at least since Keynes’ (1936) General Theory. This paper aims to provide the critical point of existing literature related to the determinants of cash holding in order to find directions for further research in this topic.